A Proposal for the Attribution of Market Leakage to CDM Projects - Timo Kuosmanen; Frank Vöhringer; Rob B. Dellink (Hamburg Institute of International Economics (HWWA), 2004)
Economic models suggest that in many cases, market leakage rates of greenhouse gas abatement reach the two-digit percentage range. Consequently, the Marrakesh Accords require Clean Development Mechanism (CDM) projects to account for leakage. Despite this, most project proponents neglect market leakage for their project, because the influence of an individual project on market prices seems to be negligible. Insufficient leakage accounting is facilitated by a lack of theories and applicable proposals regarding the quantification and attribution of leakage effects. The aim of this paper is to develop a proposal for the attribution of market leakage effects to CDM projects. To this purpose, we identify the transmission mechanisms for CDM project leakage, investigate the current practice of leakage accounting, and analyse alternative attribution methods for leakage effects that are transmitted through price changes. We find that project-specific approaches must fail to take account of such leakage effects. Consequently, we propose to estimate aggregate market leakage effects and attribute them proportionally to individual projects. Our proposal is based on commodity-specific leakage factors which can be applied by project developers to any emission reductions that are associated with a project's leakage-relevant demand or supply changes. The proposal is conservative, equitable, incentive compatible and applicable at manageable costs.
Keywords: D62; F18; Q41; Q25; 330; Climate policy; Clean Development Mechanism; market leakage; leakage accounting; sharing rules; Kohlendioxid; Luftverunreinigung; Clean Development Mechanism; Umweltökonomik; Theorie; Welt